2012
DOI: 10.1007/s00423-011-0897-1
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid cancer surgery in Germany

Abstract: Our analyses of DRG statistics provide for the first time representative population-based data of the surgical management of thyroid cancer patients in Germany. Despite an identical health care system all over Germany and existing guidelines for surgical treatment of thyroid cancer, we observed a considerable regional variation in the proportion of total thyroidectomies performed in Germany.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…And other proportions of surgeries between men and women were similar clinically. These results are in agreement with other reports [24] .…”
Section: Discussionsupporting
confidence: 94%
“…And other proportions of surgeries between men and women were similar clinically. These results are in agreement with other reports [24] .…”
Section: Discussionsupporting
confidence: 94%
“…Papillary thyroid cancer (PTC) is the most common type of thyroid malignancy but its etiology remains largely unknown [2]. The genetic predisposition of PTC has been evaluated in pedigree studies, association studies and genome wide association study [3], [4], [5], [6], [7], [8]. A series of single nucleotide polymorphisms (SNPs) were found to be associated with the risk of PTC in studies with different designs and populations, which indicated that the genetic etiology of PTC was complicated, and the results needed further investigation in independent studies to confirm the associations with PTC risk.…”
Section: Introductionmentioning
confidence: 99%
“…The calculated mortality rates can only be seen as a very good proxy for the true in-hospital mortality rates [ 28 ]. The DRG data is primarily collected for reimbursement.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, for HNC patients under palliative care, further research is needed why the patients are treated as inpatients and what has to be done that they profit from ambulatory palliative care in the future. The calculated mortality rates can only be seen as a very good proxy for the true in-hospital mortality rates [28]. The DRG data is primarily collected for reimbursement.…”
Section: Discussionmentioning
confidence: 99%